Biorefinery production technologies for chemicals and energy - Kuila, Arindam; Mukhopadhyay, Mainak (John Wiley & Sons, Inc., 2020)
"The world has shifted towards sustainable development for the generation of energy and industrially valuable chemicals. Biorefinery plays an important role in the integration of conversion process with high-end equipment facilities for the generation of energy, fuels and chemicals. The first part of the book presents the fundamentals of the biorefinery concept. The second part describes the biorefinery approach for production of several industrially important chemicals from waste biomass and agro residues. These chemicals include industrially important C4. C5 and C6 chemicals, propylene glycol, glycerol byproducts, dyes and inks etc. Each and every chemical has its own industrial value and the book describes the production processes and strategies at the industrial level. The final part of the book describes the various biorefinery approaches and economic analysis for the different types of biofuel production"--